Identification of benzopyrone as a common structural feature in compounds with anti-inflammatory activity in a zebrafish phenotypic screen - Anne L. Robertson (Disease Models & Mechanisms, 2016)
Neutrophils are essential for host defence and are recruited to sites of inflammation in response to tissue injury or infection. For inflammation to resolve, these cells must be cleared efficiently and in a controlled manner, either by apoptosis or reverse migration. If the inflammatory response is not well-regulated, persistent neutrophils can cause damage to host tissues and contribute to the pathogenesis of chronic inflammatory diseases, which respond poorly to current treatments. It is therefore important to develop drug discovery strategies that can identify new therapeutics specifically targeting neutrophils, either by promoting their clearance or by preventing their recruitment. Our recent in vivo chemical genetic screen for accelerators of inflammation resolution identified a subset of compounds sharing a common chemical signature, the bicyclic benzopyrone rings. Here, we further investigate the mechanisms of action of the most active of this chemical series, isopimpinellin, in our zebrafish model of neutrophilic inflammation. We found that this compound targets both the recruitment and resolution phases of the inflammatory response. Neutrophil migration towards a site of injury is reduced by isopimpinellin and this occurs as a result of PI3K inhibition. We also show that isopimpinellin induces neutrophil apoptosis to drive inflammation resolution in vivo using a new zebrafish reporter line detecting in vivo neutrophil caspase-3 activity and allowing quantification of flux through the apoptotic pathway in real time. Finally, our studies reveal that clinically available ‘cromones’ are structurally related to isopimpinellin and have previously undescribed pro-resolution activity in vivo. These findings could have implications for the therapeutic use of benzopyrones in inflammatory disease.